PROVIDING SNACKS TO IMPROVE DIETARY ADHERENCE, ADEQUACY OF NUTRITION INTAKE AND QUALITY OF LIFE FOR HEMODIALYSIS PATIENTS - Sa'bania Hari Raharjeng (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2022)
This study aims to determine the effect of high-energy-protein interlude on increasing dietary compliance, nutritional intake adequacy and quality of life of hemodialysis patients. This research is a pre-experimental study with a one group pre-test and post-test design. The number of samples in this study was 71. All research subjects were patients undergoing hemodialysis treatment at Dr. Sardjito Hospital Yogyakarta. Patients will be given high-energy and protein snacks twice a day for 21 days. The sample it self was selected by using the consecutive sampling method. Data analysis using McNemar test and Multiple Logistics Regression. The results showed that there was a significant increase in dietary compliance and nutrient intake during the intervention, but after the intervention was completed, decreased compliance and nutritional intake. So that there was no significant difference in dietary adherence between before and after the intervention (p = 0.32) and there was no significant increase in the adequacy of nutrient intake between before and after the intervention. There was a significant difference between the quality of life scores before and after being given a snack (p = 0.01). Multivariate analysis showed that energy intake, fat intake, and length of hemodialysis period could be used to predict poor quality of life of hemodialysis patients (R2 = 0.125; AIC = 72). The provision of snacks can help to increase the average intake of nutrients to meet the intake of nutrients and the quality of life of hemodialysis patients.